An accident record linkage study: the first step towards an injury strategy - Marco Raul Soares Amorim (2013)
Portugal, as a European country, has set a target for cutting injuries. However, the real magnitude of the road safety and the scale of long-term impairment and associated socio-economic costs are not well known given the common problems of under-reporting and misreporting under current arrangements. The problem is that current figures on serious injuries are generalized, and consequently reference values are usually estimates. Thus, in presence of these problems, comparison across European countries has been a complex task Knowing that no single database will provide enough information to give a complete picture of road traffic injuries and to fully understand underlying injury mechanisms, the use of health sector data to complement police data is recognized as being the key for future improvements in road safety analysis. Therefore, an accident record linkage is the first step towards a wide road safety analysis, comprising the knowledge of the accident site and the consequences of the accident covering the period between the time immediately after the accident and the discharge time of the accident victim(s). In this context, this paper will provide the first assessment of the needs of a linked data system, to be applied in Portugal, in response to EU strategy on serious road injuries. This kind of data may be particularly important to analyze, understand, and define the vulnerable road users' (VRU) traffic safety issues core, and to propose and evaluate practical accident countermeasures. In fact the progress in the safe mobility has not been as consistent as desirable in part because of the lack of knowledge of the real situation.